(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الصحية, 2018)
يعتبر الحليب غذاءً متوازناً فهو يحتوي على كل المغذيات الضرورية للإنسان. يوجد العديد من الطرائق والمواد التي يتم غش الحليب بها كغش الحليب بإضافة الماء، اليوريا، النشاء والجيلاتين وغيرها. يؤدي غش الحليب ومنتجاته إلى تقليل قيمتها الغذائية كما أن لبعض المواد المستخدمة في الغش تأثيرات ضارة على الجسم. تعتبر اليوريا مكون طبيعي للحليب حيث تنتج عن استقلاب البروتين في الجسم لكن يمكن غش الحليب بها وتتم إضافتها إلى منتجات الحليب كبديل عن البروتين إثر تمديد الحليب بالماء كونها غنية بالآزوت، إلا أنها تؤدي إلى تأثيرات ضارة عند التعرض المزمن لها خاصة على الكلى. يهدف هذا البحث إلى تحديد اليوريا كمياً في بعض منتجات الحليب المتوافرة في السوق المحلية عن طريق تطبيق الطريقة الطيفية اللونية باستخدام كاشف Erlich (Para Di Methyl Amino Benzaldehyde). شملت الدراسة 66 عينة توزعت ما بين 17 عينة حليب سائل مجموعة من محلات البقالة المحلية, 10 عينات حليب سائل مسوقة من قبل بعض الشركات المحلية والمستوردة, 9 عينات لبن مجموعة من محلات البقالة وعينتين لبن مسوق من إنتاج شركة محلية, 16 عينة حليب مسحوق خاص بعمر فوق السنة و12 عينة حليب مسحوق للرضع. أظهرت الدراسة أن قيم اليوريا في جميع العينات المدروسة كانت ضمن الحدود المسموح بها مما يدعو للاستنتاج أن عملية غش الحليب ومنتجاته باليوريا مازالت طريقة غير شائعة في بلادنا. Milk is a balanced food contains all the nutrients necessary for human. Many methods and substances are used in milk adulteration like adding water, urea, starch, gelatin, etc. Milk adulteration reduces the nutritional value and some substances have harmful effects in human. Urea is a natural component of milk, and final product of protein in humans’ body. Urea can be used in milk adulteration as an alternative to protein after the dilution of milk with water since urea is rich in nitrogen. Urea has adverse effects mainly on the kidneys at the chronic exposure. This study aimed to determine urea in some milk products available in the local market by applying the spectrophotometric method using Erlich reagent (Para Dimethyl Amino Benzaldehyde). This study included 66 samples: 17 liquid milk samples collected from local grocery stores, 10 liquid milk samples produced by some local and imported companies, 9 yogurt samples collected from local grocery stores, 2 yogurt samples produced by a local company, 16 powdered milk samples, and 12 infant’s powdered samples. The results showed that urea values were within the permissible limits in all of the studied samples. That means milk adulteration with urea might not be common in Syria.